Ka‐band phased patch array antenna integrated with a PET‐controlled phase shifter. Issue 3 (25th November 2015) - Zhang, Yifei; Bai, Jian; Shi, Shouyuan; Prather, Dennis W.
ABSTRACT: In this article, a 4 × 4 linear‐phased patch array antenna, consisting of four 1 × 4 patch subarrays and a true time‐delay multiline phase shifter, is proposed on a thin film liquid crystal polymer substrate at Ka‐band. The patch antenna is designed with a gain of 6 dBi at 35 GHz and a bandwidth of 23% centered at 35 GHz. To enhance the gain and symmetrize the beam patterns of the 4 × 4 array, a 1 × 4 patch subarray in the E ‐plane was designed and characterized. The subarray produces an enhanced gain of 11 dBi and a wide beamwidth of ±38° in the H ‐plane for beam steering. The proposed phase shifter comprises a 1 × 4 microstrip line power splitter and a piezoelectric transducer‐controlled phase perturber. A large phase variation of up to 370° and a low insertion loss of less than 2 dB were demonstrated for the phase shifter at Ka‐band. The integrated phased array attains a gain of 15.6 dBi, and a continuous true‐time delay beam steering of up to 33 ± 1° from 31 to 39 GHz. © 2015 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:199–208, 2016.